2021
DOI: 10.1101/2021.05.17.21257335
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduction in COPD exacerbations during COVID-19: a systematic review and meta-analysis

Abstract: Background Reports have suggested a reduction in exacerbations of chronic obstructive pulmonary disease (COPD) during the coronavirus (COVID-19) pandemic, particularly hospital admissions for severe exacerbations. However, the magnitude of this reduction varies between studies. Method Electronic databases were searched from January 2020 to May 2021. Two independent reviewers screened titles and abstracts and, when necessary, full text to determine if studies met inclusion criteria. A modified version of the Ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…We used the new BTS quality standard and measured the decision to mask time (Table 1). Despite 45.8% fewer patients receiving NIV, in concordance with recent reports of fewer COPD exacerbation presentations, 5 we saw an increased median (interquartile range) decision to mask time, from 61 min (43-77) to 132 min (65-179), in 2020 (p < 0.0001) (Table 1). Following this delay in NIV set up, we saw increased deaths (4 [4.8%] vs. 8 [17.8%], p = 0.014) associated with lower blood gas pH levels (7.34 [7.30-7.37] vs. 7.62 [6.53-9.17], p = 0.019) and higher partial pressure of carbon dioxide (pCO 2 ) levels (8.59 [7.79-10.37] vs. 7.62 [6.53-9.17], p < 0.001) in 2019 versus 2020 (Table 1).…”
supporting
confidence: 89%
“…We used the new BTS quality standard and measured the decision to mask time (Table 1). Despite 45.8% fewer patients receiving NIV, in concordance with recent reports of fewer COPD exacerbation presentations, 5 we saw an increased median (interquartile range) decision to mask time, from 61 min (43-77) to 132 min (65-179), in 2020 (p < 0.0001) (Table 1). Following this delay in NIV set up, we saw increased deaths (4 [4.8%] vs. 8 [17.8%], p = 0.014) associated with lower blood gas pH levels (7.34 [7.30-7.37] vs. 7.62 [6.53-9.17], p = 0.019) and higher partial pressure of carbon dioxide (pCO 2 ) levels (8.59 [7.79-10.37] vs. 7.62 [6.53-9.17], p < 0.001) in 2019 versus 2020 (Table 1).…”
supporting
confidence: 89%
“…Multiple studies subsequently reported a substantial reduction in hospitalisations due to asthma and chronic obstructive pulmonary disease (COPD) exacerbations, temporally associated with introduction of COVID-19 infection control measures [5], likely because people avoiding SARS-CoV-2 were also avoiding viruses that cause exacerbations [6].…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of all trials conducted in Europe in pre-COVID-19 times were on respiratory diseases 13,14 . Due to COVID-19 containment measures that intend to attenuate SARS-CoV-2 transmission, respiratory disease transmission is altered at the population scale, and/or there might be under-reporting of respiratory diseases to healthcare services (see a recent systematic review by Alqahtani et al (2021) 15 ).…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
“…Due to COVID-19 containment measures that intend to attenuate SARS-CoV-2 transmission, respiratory disease transmission is altered at the population scale, and/or there might be under-reporting of respiratory diseases to healthcare services (see a recent systematic review by Alqahtani et al . (2021) 15 ). Recent reports show that seasonal dynamics of common respiratory tract infections (RTIs) have almost vanished during the COVID-19 pandemic 1619 .…”
Section: Introductionmentioning
confidence: 99%